The Context of Languages and Pedagogical Aspects in Teen Lit Novels - Cynantia Rachmijati; Anita Anggraeni (Universitas Sanata Dharma, 2018)
Teen-lit is one of the teenage novel genres. Teen-lit comes from the word teen and lit which means literature or written works. Teenlit novel means written works made by teenager telling stories revolved in teenagers life. This research aims at knowing how many and what types of code mixing are found inside the novel, along with the pedagogic aspects in it. The subjects of the research are chick-lit teen-lit genre entitled Aviredie by Alline, Grow up! by Sucia Ramadhani, Pertama kalinya! by Sitta Karina and Oppa and I by Orizuka and Lia Indra; and lad-lit teen lit genre entitled Hidden agenda by Jacob Julian, Marmut merah jambu by Raditya Dika, School of chemistry by Al Dhimas. The research method is qualitative method. The research results show that teen-lit mostly use more of outer code mixing in English as their speech rather than inner code mixing in their mother tongue (Indonesia), and mostly contains of social, cultural and moral paedagogic aspects. Educators especially English teacher can use this teen lit novels as one of the teaching materials.Keywords : pedagogical aspects, teen-lit